2016
DOI: 10.1007/s10877-016-9869-x
|View full text |Cite
|
Sign up to set email alerts
|

One operator’s experience of ultrasound guided lumbar plexus block for paediatric hip surgery

Abstract: Lumbar plexus block has been shown to be effective for providing postoperative analgesia after major hip surgeries in children. The goal of the study was to evaluate the feasibility of ultrasound guidance during lumbar plexus block in children undergoing hip surgery for congenital hip dislocation. After obtaining local institutional ethical committee approval and parental informed consent, ASA I or II, 1-6 years old children undergoing hip surgery were included into the study. Lumbar plexus block was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Ultrasound-guided positioning has obvious advantages over nerve stimulator positioning. Under ultrasound guidance, the relationship between the needle and nerves as well as the surrounding vascular tissues can be directly observed and the success rate of block is improved, thus reducing the occurrence of complications such as kidney and nerve damage [ 6 , 7 ]. In this study, the “Shamrock method” was used to guide continuous lumbar plexus block and continuous femoral nerve block and to compare the analgesic effects and hemodynamic effects of the two ways on elderly patients after TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound-guided positioning has obvious advantages over nerve stimulator positioning. Under ultrasound guidance, the relationship between the needle and nerves as well as the surrounding vascular tissues can be directly observed and the success rate of block is improved, thus reducing the occurrence of complications such as kidney and nerve damage [ 6 , 7 ]. In this study, the “Shamrock method” was used to guide continuous lumbar plexus block and continuous femoral nerve block and to compare the analgesic effects and hemodynamic effects of the two ways on elderly patients after TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Gürkan et al. showed that the shamrock approach could prolong the analgesic time after hip surgery [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…With this approach, satisfactory sensory changes were achieved in a high percentage of patients. Gurkan used this technique on children 1‐6 years of age having open surgery for congenital hip dislocation and reports block duration of 8‐12 hours and only one patient requiring morphine.…”
Section: Discussionmentioning
confidence: 99%
“…With this approach, satisfactory sensory changes were achieved in a high percentage of patients. Gurkan 16 | 293 of the block under general anesthesia. We report no serious complications in our study, but the study was not powered to detect complications.…”
Section: Discussionmentioning
confidence: 99%